1995
DOI: 10.1246/cl.1995.771
|View full text |Cite
|
Sign up to set email alerts
|

The Copper(I) Iodide-promoted Allylation of Vinylstannanes with Allylic Halides

Abstract: The stereospecific allylation of vinylstannanes with allylic halides proceeded in the presence of copper(I) iodide in DMSO-THF at room temperature. The stereospecificity of the reaction was dependent on the structures of vinylstannanes and allylic halides, and also the leaving group of allylic halides employed. Concerning the regioselectivity regarding allylic system, higher α-regioselection was observed in the reactions of allylic chlorides than in those of the corresponding iodides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 9 publications
0
16
0
1
Order By: Relevance
“…Piers and Wong demonstrated that the intramolecular coupling of alkenyl iodides with alkenyl stannanes can be carried out in the presence of a stoichiometric amount of CuCl. [285,286] Better results were later obtained with other Cu I salts under catalytic conditions. [287][288][289][290][291] As an illustration, the cross-coupling of 98 and methyl (E)-b-iodoacrylate (99) promoted by copper(i) thiophene-2-carboxylate (CuTC) furnished 100 (Scheme 51), an intermediate in the synthesis of formamicinone.…”
Section: Reactions Initiated By the Oxidative Addition Of Stannanes Tmentioning
confidence: 99%
“…Piers and Wong demonstrated that the intramolecular coupling of alkenyl iodides with alkenyl stannanes can be carried out in the presence of a stoichiometric amount of CuCl. [285,286] Better results were later obtained with other Cu I salts under catalytic conditions. [287][288][289][290][291] As an illustration, the cross-coupling of 98 and methyl (E)-b-iodoacrylate (99) promoted by copper(i) thiophene-2-carboxylate (CuTC) furnished 100 (Scheme 51), an intermediate in the synthesis of formamicinone.…”
Section: Reactions Initiated By the Oxidative Addition Of Stannanes Tmentioning
confidence: 99%
“…The chemical shift of the trimethylsilyl protons of the 2a-metha was observed at 0.18 ppm, but that of its Z-isomer was reported to appear at −0.17 ppm. [14] CuI-mediated cross-coupling of (Z)-(n-Bu) 3 SnCAr CHSiMe 3 1 with allyl halides in DMSO-THF The transmetallation of Sn → Cu → Pd suggested by Liebeskind et al [59] in the reaction of simple vinylstannane with organic halides and the copper(I) iodide-mediated reaction of simple vinylstannane with allyl halides reported by Takeda et al [60] stimulated us to examine the copper(I) iodide-mediated crosscoupling of (Z)-silyl(stannyl)ethenes 1 with allyl halides in a polar aprotic solvent, particularly a DMSO-THF solvent. No precedent has been reported for the reaction of 1 with allyl halides in the sole presence of copper(I) halide.…”
Section: Optimization Of Reaction Conditions Outlined In Schemementioning
confidence: 95%
“…Spectral data ( 1 H-NMR, 13 C-NMR, 29 Si-NMR, IR, LRMS and HRMS) agreed well with those from the expected structure. Copper(I) iodide-mediated reaction in DMF or in DMSO-THF solvent [60] readily occurred at room temperature to give 3a in 43-80% yields. Among them, CuI-mediated reaction in DMSO-THF recorded the highest yield (80% isolated-yield) of 3a.…”
Section: Cui-mediated Reaction Of (Z)-(n-bu) 3 Sncar Chsime 3 1 With mentioning
confidence: 99%
“…No precedent was found for the copper(I) iodide-mediated cross-coupling of (Z)-(R 3 Sn)CR CH(GeR 3 ) with allylic halides, while copper (I) iodide 52 has been reported to mediate the coupling reaction of a simple vinylstannane, 1-(tri-n-butylstannyl)-1-phenylethene, with an allyl halide. (Z)-Germyl(stannyl)ethenes 1 are much more congested compared with 1-(tri-n-butylstannyl)-1-phenylethene.…”
Section: Cui-mediated Cross-coupling Of (Z)-germyl(stannyl)ethenes Wimentioning
confidence: 99%